The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/00029157.2017.1289465
|View full text |Cite
|
Sign up to set email alerts
|

Self-Talk Monitoring and Utilization for Enhancing Hypnotic Induction

Abstract: In contemporary hypnosis, language constitutes the hypnotist's rudimentary instrument for developing and utilizing the hypnotic trance. In the current article, the author proposes a theoretical and clinical approach for using patient self-talk during hypnotic induction by discussing the influence of self-talk on consciousness regulation. The article includes some historical background on the use of language during hypnotic communication and demonstrates some clinical applications of patients self-talk in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Respondents' under stressful conditions when exposed to classical music or music experienced less stress, less anxiety, become more calm [38], [39], [41]- [43], and relieve level of stress [44]. It was also revealed that depression was reduced through music [40], [45]- [47].…”
Section: Resultsmentioning
confidence: 99%
“…Respondents' under stressful conditions when exposed to classical music or music experienced less stress, less anxiety, become more calm [38], [39], [41]- [43], and relieve level of stress [44]. It was also revealed that depression was reduced through music [40], [45]- [47].…”
Section: Resultsmentioning
confidence: 99%
“…Educational self-talk interventions teach people about their organic self-talk to improve their self-regulation. Accordingly, self-talk was most commonly referred to as positive self-talk (Table 1) and described as a self-regulatory mechanism (Goldberg et al, 2018; Meyerson, 2017; Sassi-Dambron et al, 1995). As expected, educational self-talk interventions aimed to strengthen the goal-directed use of self-talk.…”
Section: Self-talk Literature Reviewmentioning
confidence: 99%
“…Nor have researchers ascertained whether inductions based on client preference (e.g., relaxation vs. imagery based) are particularly effective. Still, in our clinical work we solicit preferences and actively coconstruct inductions with clients (see Meyerson, 2017), just as we do when we cocreate suggestions to target a specific problem or issue. We further advocate inductions that minimize perceptions of failure, bolster positive expectancies, and provide initial indications of responsiveness (see example of such a "fail safe" induction, Lynn, Kirsch, & Rhue, 1996).…”
Section: Do Not Be Too Concerned About the Type Of Inductionmentioning
confidence: 99%
“…Targeted hypnotic suggestions can disrupt incipient streams of negative associations that recruit other associations, build momentum, and engender negative moods or trigger dysfunctional behavior patterns. As maladaptive, repetitive, and ruminative automatic thoughts (e.g., “I am not good enough”) are often highly salient and their validity unquestioned, they can be legitimately explained to clients as dysfunctional self-talk, inner speech, or self-suggestions that are amenable to being monitored, modified, and tested for their accuracy (Lynn & Kirsch, 2006; Meyerson, 2017; Yapko, 2013). In the case of depression, self-talk coalesces around themes of low self-esteem, worthlessness, and inadequacy, and in the case of anxiety, themes of anticipated threat or negative outcomes.…”
mentioning
confidence: 99%